Sustainability of the Small-Scale Tea Processors in Kenya - Kiende, Gatimbu K. (University of Embu, 2019)
The tea industry remains vital for export earnings, employment creation and GDP growth. These processors, however, are experiencing a persistent rise in their cost of production. They have pursued sustainability initiatives to scale down production costs. However, the outcome of such initiatives has not been measured. This study thus sought to determine the sustainability of the small-scale tea processors in Kenya. A pragmatic paradigm research philosophy was adopted. All the 54 factories were considered for the study. Primary data entailed interviews with Key Informants. Secondary data was obtained from factory documents and reports, peer-reviewed publications and grey literature. Data Envelopment Analysis was used to compute the environmental efficiency scores. Tobit regression was applied to determine the influential factors of firm variation in environmental efficiency. Stochastic Frontier Analysis was used to determine the technical efficiency scores, as well as determinants in a one-step estimation equation. A Meta-technical efficiency method was used to establish regional efficiency estimates. Finally, Emergy methodology was used to assess the ecological/economic sustainability of these processors. In sum, the thesis contributes to both literature and methodology. Results showed that the tea processors were environmentally inefficient, recording a mean efficiency index of only 49%. Factories have the ability, therefore, to reduce 51% of detrimental environmental inputs without compromising output. Fortunately, efficiency was on an upward trajectory, rising from 29.4% in 2014 to 36.8% in 2016. Further, environmental efficiency affected the profitability of these processors. Results showed a negative effect of environmental efficiency on profitability. Worth noting, 81.3% of factories that had good environmental performance (0.8-1.0) had low profitability, ranging from -0.25% to 1.23%. Factories that were environmentally efficient had a 0.7% lower chance of being profitable. For the second objective, the technical efficiency level derived from the regional frontier was 76%, while that from the meta-frontier was 74%. The technological gap ratio was 97%. Thus, input costs could be reduced by 24% without compromising the potential output. The overall persistent inefficiency for the pooled sample was about 20%, with a residual inefficiency of about 5%. This implies that structural and managerial aspects were involved in the greater inefficiency of the smallscale tea processors. No significant relationship between technical efficiency and profitability was observed. For the third objective, the total Emergy for the purchased non-renewable resources was 93.4%, purchased renewable resources registered 6.3%, and renewable resource was 0.3%. Results showed that the small-scale tea processors relied heavily on purchased non-renewable resources, hence rendering the processing subsystem ecologically/economically unsustainable. The results further showed that the small-scale tea processing sub-systems were profitable, with an average economic output/input ratio of about 2.5. The policy implication of these findings is that the government should offer incentives for the adoption of improved environmental technologies. For example, offering a tax subsidy for new technologies adopted should be considered. For the small-scale tea processors’ management, they should seek alternative sources of finance that are cheaper or negotiate for better terms of borrowing with the financiers. In addition, the processors might consider automating some factory processes and incorporate the use of renewable energies, for example, solar power and gasifiers. Further, they may consider issuing a green instrument that simultaneously reduces the cost of capital and ecological impact.